Errors In Spoken Production Made By Students Of MAN 1Boarding School Surakarta - Fadhilah Jati, Anida, Prof. Dr. Endang Fauziati, M.Hum (2017)
This research paper is aimed to describe the types of error, the dominant error, the frequency of error, and the sources of error made by students of MAN 1 Boarding School Surakarta in doing speech event. The subject of this research is twenty female students in doing speech event at Boarding School MAN 1 Surakarta. The type of this research is descriptive qualitative research. In collecting data researcher records, listens, makes a sript, reads a sript, and selects the data.. To analyze the types of errors, researcher uses theory of Clark and Clark (1997), Dulay, Burt, Krashen, and Richard (1982). The finding shows that researcher found three types of errors namely speech error, morphological errors and syntactical errors. In speech error researcher found silent pause (9,59%) filled pause errors (38,37%), repeats (16,97%), false retraced (4,42%), correction (0,37%), interjection (1,10%), stutters (6,64%).In the morphological error researcher found two types of errors namely pronunciation (0,74%), and vocabulary (7,01%). In syntactical errors there are omission of third singular pronoun (2,21%), verb infinitive instead of verb ing (1,84%), in infinitive instead of verb participle (1,84%), selection of verb after modality (2,58%), omission of [be] ( 2,58%), wrong selection of be [is, are] singular instead plural (1,48%), omission bound morpheme [-s] as plural (0,74%), and the last preposition or (1,48%). The dominant error is speech errors especially filled pause. The writer found two sources of errors namely cognitive reason and psychological reason.